Synthesis and characterization of a phosphine oxide based poly(arylene ether ketone) and blends with poly(2, 6-dimethyl-1, 4-phenylene oxide) for gas separations. (28th February 2018) - Narang, Gurtej S.; Moon, Joshua D.; Zhang, Wenrui; Miller, Gregory C.; Choudhury, Shreya Roy; Shaver, Andrew; Vondrasek, Britannia; Lesko, J.J.; Fallon, Jacob J.; Bortner, Michael; D'Ambra, Colton; Freeman, Benny D.; et al.
Abstract: Membranes were prepared from blends of poly(2, 6-dimethyl-1, 4-phenylene oxide) (PPO) and two poly(arylene ether ketone) random copolymers, one that contained a phosphine oxide monomer (POPAEK) and one that did not (BPAPAEK). Two Tg's for all of the blends except for those with the lowest molecular weight PPO showed that these were two-phase materials. Partial crosslinking with UV light resulted in materials with decreased permeabilities and increased gas selectivities. Blend compatibility was improved with the phosphine oxide. Permeabilities of PPO/POPAEK blends were closer to a miscible additivity model than the PPO/BPAPAEK blends, suggesting that POPAEK has more favorable interactions with PPO. This was reinforced by the fact that blends containing the POPAEK did not display significant reductions in tensile properties even at intermediate compositions where the blend interfacial area was largest. SEM images of fracture surfaces of the blends with high concentrations of PPO showed a finer microstructure with the POPAEK copolymer. Graphical abstract: Highlights: Phosphine oxide polyarylene ether ketones were blended with PPO and UV crosslinked. Gas permeation selectivity of PPO was improved while maintaining high permeability. Phosphine oxide increased compatibility of the polyarylene ether ketone with PPO.